The international entrepreneurial firm's social networks - Ferreira, Manuel Portugal (2021)
This paper investigates theoretically the importance and impact of the international entrepreneurial firms’ (IEFs) social networks on selected firms’ strategies. We focus specifically on some core attributes of IEFs and the impact of social networks on such strategies as the choice of the foreign markets to operate and the foreign entry modes. The social networks are a major driver of the internationalization from inception and help in overcoming a variety of physical and social resource limitations as well as transactional hazards. We conclude that it is likely that both some fundamental characteristics of the IEFs and those of the foreign markets entered account for these firms reliance on their social networks.